Run it like a business : strategies for arts organizations to increase audiences, remain relevant, and multiply money-- without losing the art - Bergauer, Aubrey (BenBella Books, Inc., 2024)
TEDx speaker Aubrey Bergauer--"the Steve Jobs of classical music"--reveals how to run a successful arts business in the post-pandemic era, adapting for-profit methods for not-for-profit goals. In the US alone, the arts are a $763 billion sector whose 100,000+ organizations serve almost every community in the nation. There's no reason arts organizations should struggle to make ends meet. And now, with arts-tested strategies from Aubrey Bergauer, they won't. This foolproof guide shows how to reach new levels of engagement while always putting art first. Running your arts organization like a business is your path forward to: Grow audiences and keep them coming back again; Make our organizations more inclusive; Get younger attendees in the seats and on the donor rolls; Generate millions more dollars in revenue; Continue to create the art we love without the stress of figuring out how to afford it. Just because arts organizations are non-profits doesn't mean they shouldn't make money; it means the money they make goes back to fund the mission -- whether that's music, visual arts, theatre, dance, or one of many other mediums that enrich our lives. The for-profit world knows how to achieve success across customer engagement, user experience, company culture, the subscription economy, technology and media, new revenue streams, and brand relevance. Run It Like a Business provides a powerful, proven framework to help all arts organizations revitalize their economic engines and ultimately serve the arts and its patrons.--